Population parameters of the shrimp Xiphopenaeus kroyeri (Heller, 1862) (Crustacea, Penaeidae), caught by artisanal fisheries in Anchieta, Espírito Santo State - doi: 10.4025/actascibiolsci.v35i2.13408 - Eutrópio, Frederico Jacob (2012)
The fishery on Penaeidae shrimp is done all over the Brazilian coast, especially the seabob shrimp (Xiphopenaeus kroyeri). It is captured in large quantities in the Southeast and Southern Brazil. In order to study the population structure of X. kroyeri from Anchieta Municipality, Espírito Santo State, during the period from January to December 2008, monthly samplings with one-hour-long were conducted to verify the number of individuals, biomass, sex, total length and gonad maturity stage. The specimens had total length ranging from 2.96 to 9.96 cm, and females were larger than males. It is suggested that the population of X. kroyeri presents patterns of recruitment and reproduction similar to those of the Northeast region. The estimated size of first gonadal maturation was 4.5 and 6.9 cm for males and females, respectively. The fishing operates on a stock composed of predominantly adult males and juveniles and adult females. The mesh size of the nets and the high plant biomass in the fishing areas may be contributing to the increased catch of juveniles, undermining the recruitment of X. kroyeri.